PENGATURAN PERLINDUNGAN HUKUM TERSANGKA YANG MENGALAMI TINDAK KEKERASAN DALAM PROSES PENYIDIKAN DIKAITKAN DENGAN UPAYA PERLINDUNGAN HAK ASASI MANUSIA TERSANGKA - satria, Beni; Indra, Mexsasai; ', Erdiansyah (Jurnal Online Mahasiswa (JOM) Bidang Ilmu Hukum, 2017)
Law enforcement officers often consider that torture is best and easiest way to be able to extract information from a suspects. In fact, we often find media reports about the violence committed by the investigator in the investigation process to get confession from someone who allegedly committing a crime.As for the purpose of writing this thesis is to determine arrangements of legal protection to suspects who experienced crimes of violence in the investigation process and criminal accountability of violence committed by investigators associated with efforts to protect the human rights of suspects.In writing this thesis, the author use the normative research methods, which in this study by a literature review. To draw a conclusion from the collected data, the authors using data analysis techniques deductive, by draw a conclusion from general to specific conclusion.The conclusion that can be derived from this research are: First, the setting about law protection of abused suspects in the investigation process does not have special regulations, so there are still many loopholes for law enforcement officials committing acts of violence in the investigation process. Second, the criminal liability of the investigator who do violence to the suspect did not go as mandated by chapter 422 of KUHP, where there are many investigators who commit acts of violence in performing its duties escape from legal responsibility. As well as ineffective oversight of the process of investigations conducted by the superior based on rules of Criminal Investigation about supervisory investigation and the need for revision of these regulations in order to optimize the process of monitoring the investigation.Keywords: Regulation - Legal Protection - Suspect